Arte terapia y su influencia en el desarrollo psicomotriz en los niños con síndrome de down de la Unidad Educativa Especializada Cotopaxi de la provincia de Cotopaxi, cantón Latacunga, parroquia Ignacio Flores, barrio Betlemitas en el año lectivo 2014-2015 - Shingón Collahuazo, Iveth Adriana (2015)
This research aims to develop a guide to art therapy with different artistic activities for psychomotor development in children with Down syndrome, identifying their skills and applying different strategies and methodologies according to the degree of disability of students in Special Education Unit Cotopaxi is of vital importance in the field of education, research techniques that helped us was to gather information and interview survey conducted by the authorities, teachers, parents and structure charts and graphs allowing for conducting respective interpretation the results thus forming conclusions and recommendations as personal contributions. As teachers we must investigate new techniques for the progress of psychomotor different areas managing to improve their creativity and imagination given the motivation to encourage them to acquire new knowledge, working in groups to the integral progress of children in society and valuing each one of his works they perform in the classroom, getting to work with different art therapy activities stipulated by raising their self-esteem and confidence to their environment independently.